2022
DOI: 10.1155/2022/4280691
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physiological Levels of Cortisol and Adrenocorticotropic Hormone upon Hospitalization Can Predict SARS-CoV-2 Mortality: A Cohort Study

Abstract: There is some indication that coronavirus disease 2019 (COVID-19) causes hypothalamic-pituitary-adrenal axis insufficiency. However, being on glucocorticoids makes it difficult to fully investigate this axis, especially in patients with severe COVID-19. We aimed to discover if there was a connection between blood total cortisol and adrenocorticotropic hormone (ACTH) levels and mortality in patients with COVID-19. In Iran, 154 hospitalized patients with COVID-19 were studied in a prospective cohort study. ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 32 publications
0
23
0
6
Order By: Relevance
“…A recent metaanalysis of published data revealed significantly higher levels of cortisol in patients with severe COVID-19 in comparison with those with mild-to-moderate disease forms [59] . However, cortisol levels were substantially lower in fatal cases of COVID-19 compared to survivors [60] . The apparent contradiction in some of these results might be explained by the heterogeneity of patient samples as well as testing protocols used.…”
Section: Pituitary Pathology In the Context Of Covid-19mentioning
confidence: 82%
“…A recent metaanalysis of published data revealed significantly higher levels of cortisol in patients with severe COVID-19 in comparison with those with mild-to-moderate disease forms [59] . However, cortisol levels were substantially lower in fatal cases of COVID-19 compared to survivors [60] . The apparent contradiction in some of these results might be explained by the heterogeneity of patient samples as well as testing protocols used.…”
Section: Pituitary Pathology In the Context Of Covid-19mentioning
confidence: 82%
“…Among them, 32 % (9/28) of patients had central adrenal insufficiency and fulfilled the criteria of CIRCI ( < 10.8 μg/dl) [62]. Similarly, in another study with a larger number of COVID-19 patients (n = 154), significantly lower cortisol but not ACTH plasma levels were found among non-survivors [63]. Finally, adrenal hypocortisolism (cortisol < 15 μg/dl in moderate-to-severe group vs. < 6 μg/dl in mild group), was more frequently found (38.5 vs. 6.8 %) in patients with severe COVID-19 (n = 35) as compared to patients with mild disease group (n = 49) [64].…”
Section: Adrenal Gland Function In Patients With Covid-19mentioning
confidence: 85%
“…Cortisol levels were substantially lower in those who died (311.7 (273.1-394.5) nmol/L) than in patients who were discharged (460.7 (344.8-598.6) nmol/L) (p = 0.003), while ACTH levels were unaffected. According to the logistic model, cortisol levels that rose by one unit correlated with a 26% lower mortality risk [66]. Overall, the existing evidence does not consistently support an association of severe COVID-19 with the presence of reduced or increased cortisol.…”
Section: Clinical Data During Acute Covid-19 Infectionmentioning
confidence: 86%
“…By contrast, the most recent findings revealed that individuals with SARS-CoV-2 who had lower cortisol levels had a greater fatality rate [66]. A total of 154 hospitalized patients with COVID-19 were studied in a prospective cohort study.…”
Section: Clinical Data During Acute Covid-19 Infectionmentioning
confidence: 97%
See 1 more Smart Citation